Lean Logistics to reduce logistics costs in an SME, Lima - 2024 - Asencios Soria, Patricia Sofia; Miñan Olivos, Guillermo Segundo (LACCEI, 2024)
The objective of the study was to implement Lean Logistics strategies to reduce logistic costs in a small and medium-sized enterprise (SME) located in Lima during the year 2024. This applied research adopted a quantitative approach, with a descriptive scope and was conducted through a cross-sectional, non-experimental design. The findings revealed a 9% increase in logistic costs between the years 2022 and 2023, escalating from 12,100 to 13,200. Various operational deficiencies were identified, including the absence of a standardized storage procedure, disorganization in the warehouse, ineffective product distribution, delays in deliveries, order errors, production delays, sales losses, and inefficient inventory management. To address these issues, improvements were proposed following Lean principles, highlighting the implementation of the Value Stream Mapping (VSM) tool to optimize timings and reduce costs associated with overtime. The ABC classification strategy was recommended to minimize expenses on high-cost products, while the 5S methodology was considered to lower inventory costs through efficient warehouse organization. Furthermore, the Kanban system was suggested to reduce picking errors and, thereby, related logistic costs. An uncertainty analysis, supported by profit matrices, determined a probable economic benefit equivalent to 289 dollars. Additionally, a sensitivity analysis confirmed that, given variations in investment and the effectiveness of logistic cost reduction, the economic benefits would remain positive in most possible scenarios, potentially reaching up to 911 dollars. In conclusion, the study determined that the adoption of Lean Logistics would significantly contribute to the reduction of logistic costs in the analyzed SME for the year 2024.